The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12889-016-3772-8
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors associated with IgG and IgM seroprevalence for human cytomegalovirus infection in adult populations of Pakistan: a seroprevalence survey

Abstract: BackgroundThe seroprevalence of human cytomegalovirus (HCMV) infection ranges from 30 to 90 % in developed countries. Reliable estimates of HCMV seroprevalence are not available for Pakistan. This study determined the seroprevalence and sociodemographic factors associated with HCMV infection in adult populations of Karachi, Pakistan.MethodsA seroprevalence survey was conducted on 1000 adults, including residents of two semi-urban communities, and visitors to a government and a private hospital. Questionnaire-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…This pattern is again reflected in that of HCMV infection. The acceleration of HCMV seroprevalence during puberty and adolescence is steeper in girls than in boys and is higher in women of childbearing age than in men in populations with relatively low HCMV seroprevalence 49 , 64 , 65 , 84 , 100 102 . Age-adjusted HCMV seroprevalence does not differ between men and women in populations with high seroprevalence 49 , 103 .…”
Section: Epidemiological Convergencementioning
confidence: 96%
See 1 more Smart Citation
“…This pattern is again reflected in that of HCMV infection. The acceleration of HCMV seroprevalence during puberty and adolescence is steeper in girls than in boys and is higher in women of childbearing age than in men in populations with relatively low HCMV seroprevalence 49 , 64 , 65 , 84 , 100 102 . Age-adjusted HCMV seroprevalence does not differ between men and women in populations with high seroprevalence 49 , 103 .…”
Section: Epidemiological Convergencementioning
confidence: 96%
“…Socio-economic status. Incidence and prevalence of CMV infection are associated with poor socio-economic status (SES), between countries as well as within countries and communities 49 , 64 , 65 , 100 , 114 116 . This includes association with crowding, in particular the number of young children in household 117 119 .…”
Section: Epidemiological Convergencementioning
confidence: 99%
“…In USA a recent analysis of CMV IgM seroprevalence in women at reproductive age also found that 97.5 % of IgM seropositive women were CMV IgG seropositive [36]. Other study performed in Pakistan, showed that 95.3 % of individuals who were IgM seropositive were equally seropositive for IgG [39]. In countries with a high prevalence of CMV infection, such as Korea and Turkey, IgG avidity testing have shown that none of the women with a pro ile of IgM and IgG positive had evidence of a primary infection [26,37].…”
Section: Discussionmentioning
confidence: 94%
“…CMV is considered as the leading intrauterine source of permanent disabilities among children such as mental retardation and hearing loss. Developed and developing countries reported high seropositive rates for CMV infection among women, e.g., US (58.3%; [ 32 ]), Europe (30–90%; [ 33 ]), India (80–90%; [ 34 ]), Pakistan (94.4%; [ 35 ]), Saudi Arabia (92–100%; [ 18 ]), and Africa (60–100%; [ 36 ]). Despite the high seropositive rate of CMV among women and the detrimental impact of CMV infection if contracted during the first trimester of pregnancy, there are several gaps in women’s knowledge of CMV [ 25 , 26 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%